To the problem of optimization of criteria for evaluating the effectiveness of providing the national security of the State - Y. V. Kobko (Law and Safety)
It has been argued that the evaluation of the effectiveness of Ukrainian national security is the activities of authorized entities carried out in the prescribed manner, which aims to establish the extent to which measures implemented by the state in the relevant direction, as well as related financial, material technical and human costs, meet the goal.